2004
DOI: 10.1177/10634266040120030101
|View full text |Cite
|
Sign up to set email alerts
|

Level and Change in Reading Scores and Attention Problems During Elementary School as Predictors of Problem Behavior in Middle School

Abstract: This study examined heterogeneity in change in reading test scores and attention problems during middle childhood and whether heterogeneity in change in these variables predicted later problem behavior. Our sample consisted of 783 students recruited from 10 Pacific Northwest schools. For both reading scores and teacher report of attention problems, latent growth curve models of annual data from Grades 3 to 6 showed statistically significant heterogeneity in initial level and change. Level and change factors fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 50 publications
1
52
0
1
Order By: Relevance
“…Few studies have included a prior history of mathematics difficulties as another potential explanatory variable when investigating the co-occurrence of reading and behavioral difficulties (Morgan et al, 2012), despite it constituting a strong possible confound of the observed co-occurrence. Additionally, many existing studies failed to control for either earlier reading problems or behavior problems (Hinshaw, 1992) or did not include other potentially relevant variables in their analyses (Fleming, Harachi, Cortes, Abbott, & Catalano, 2004). Variables such as gender, race/ethnicity, and socioeconomic status may help explain the observed co-occurrence between reading and behavioral difficulties (e.g., Feil et al, 2005; Kaplan & Walpole, 2005; Lepola, 2004).…”
Section: Methodological Limitationsmentioning
confidence: 99%
“…Few studies have included a prior history of mathematics difficulties as another potential explanatory variable when investigating the co-occurrence of reading and behavioral difficulties (Morgan et al, 2012), despite it constituting a strong possible confound of the observed co-occurrence. Additionally, many existing studies failed to control for either earlier reading problems or behavior problems (Hinshaw, 1992) or did not include other potentially relevant variables in their analyses (Fleming, Harachi, Cortes, Abbott, & Catalano, 2004). Variables such as gender, race/ethnicity, and socioeconomic status may help explain the observed co-occurrence between reading and behavioral difficulties (e.g., Feil et al, 2005; Kaplan & Walpole, 2005; Lepola, 2004).…”
Section: Methodological Limitationsmentioning
confidence: 99%
“…Externalizing behaviors such as aggression and attention problems are known to relate to lower achievement in all core academic areas (McIntosh et al 2008;Nelson et al 2004). Moreover, attention-related behaviors such as impulsivity, hyperactivity and poor concentration have been linked to academic failure and problem behaviors (Hinshaw 1992;Fleming et al 2004). This same cluster of problem behaviors have also been linked to reading difficulties (Rabiner et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…This happens because children begin to avoid reading activities both at home and in school, thereby further constraining growth in their basic reading skills, comprehension, and, eventually, cognitive functioning (Cunningham & Stanovich, 1991; Echols, West, Stanovich, & Zehr, 1996; Griffiths & Snowling, 2002; Guthrie, Schafer, & Huang, 2001; Senechal, LeFevre, Hudson, & Lawson, 1996). The children’s resulting inability to meet their classroom’s academic demands can lead to increasingly frequent feelings of frustration, agitation, withdrawal, and social isolation (e.g., Fleming, Harachi, Cortes, Abbott, & Catalano, 2004; Kellam, Mayer, Rebok, & Hawkins, 1998; Lane, Beebe-Frankenberger, Lambros, & Pierson, 2001; Wehby, Falk, Barton-Arwood, Lane, & Cooley, 2003). These feelings and behaviors may in turn further interfere with children’s learning.…”
mentioning
confidence: 99%